Simulation-based infection prevention and control training for medical and healthcare students: a systematic review - Akira Yoshikawa; Hiroyuki Ohtsuka; Keiichiro Aoki; Naonori Tashiro; Shusuke Togo; Kazuki Komaba; Satoshi Nogawa; Miwa Osawa; Megumi Enokida (Frontiers in Medicine)
IntroductionInfection prevention and control education has traditionally been conducted in a lecture-based manner, and simulation-based educational strategies have become increasingly prevalent in the field of medical education in recent years. This systematic review aimed to compare the effectiveness of the simulation-based and traditional strategies of infection prevention and control education and to show the differences between these educational approaches. Furthermore, we identified the characteristics of simulation-based strategies for infection prevention and control education.MethodSystematic reviews and meta-analyses were performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic literature search was conducted using the CENTRAL, MEDLINE, and Scopus databases for articles published between January 1990 and September 2022. This study focused on students enrolled in medical and health professional courses. As such, healthcare professionals already working in clinical settings, as well as kindergarten and elementary school students were excluded from the study. The quality of the included studies and the risk of bias in each study were assessed. A total of 254 articles were identified; 21 underwent secondary screening. Ultimately, 10 articles were selected for the final review.ResultsEducational strategies between simulation- and lecture-based education showed improvements in knowledge acquisition. There was no significant difference in the rate of improvement between the two educational strategies. The characteristics of simulation-based educational strategies included confidence in skill performance, decision-making and problem-solving skills, emotional aspects related to infectious diseases (such as fear, empathy, self-reflection, and integration of complex information), and student satisfaction.ConclusionThis systematic review suggests that simulation-based education is effective in developing students’ skills and attitudes, while traditional lecture-based methods are more suited for reinforcing students’ knowledge. Therefore, it is essential to choose educational strategies based on specific learning objectives and outcomes.Systematic review registrationThis systematic review protocol was preregistered in the Open Science Framework: https://osf.io/uj623/.